Determinación del Costo de Elaboración de los Productos Derivados del Mani en la Microempresa del Señor Juan Pablo Reyes del Cantón Olmedo, Periodo del 01 de Octubre al 31 de Diciembre del 2021 - Sarango Chamba, Elva Maritza (2022)
The present degree work called "DETERMINATION OF THE ELABORATION COST OF PRODUCTS DERIVED FROM PEANUTS IN THE MICROENTERPRISE OF MR. JUAN PABLO REYES FROM OLMEDO CANTON, IN THE PERIOD FROM OCTOBER 01 TO DECEMBER 31, 2021", was developed with the purpose of determining properly and correctly the real costs of production, with the aim of generating and providing the owner with a tool that facilitates the proper control of the production process, with significant contributions that will help the owner to make timely decisions based on economic results of his company. In order to fulfill the objectives, an inventory of raw material was first carried out, which was developed satisfactorily where only raw material was evidenced. The design of auxiliary records and control documents was carried out, which are the following; material control documents (Purchase Request, Purchase Order, Material Receipt Report, Warehouse Control Card, Material Requisition Note and Kardex) labor control documents (Payroll, Time Card and Clock Card) and control documents for indirect manufacturing costs (Cost Sheet). A production budget was made; where a sales budget was applied to identify the estimated units to be produced and what it would cost to make them. In the same way, the costs of raw materials, labor and indirect manufacturing costs used in the production process were determined through the control documents applied; A final report was prepared in which the integration of the costs incurred is presented, which was done through the statement of sold costs. Finally, with the results obtained, it can be concluded that by implementing cost accounting for production orders, it has been possible to determine the unit cost and the total cost of the products, identifying a utility with favorable profits for its owner. Therefore, it is recommended to continue maintaining this process that will make it easier to make decisions aimed at the benefit of the productive activity.